2017
DOI: 10.1049/mnl.2017.0319
|View full text |Cite
|
Sign up to set email alerts
|

Freestanding flexible polypyrrole nanotube membrane for ammonia sensor

Abstract: A simple self-sacrificed template method was used to prepare a polypyrrole (PPy) nanotubes sensor for the detection of ammonia (NH 3). Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were used to analyse the morphology of the fabricated membrane. The results show that pyrrole was uniformly polymerised around the sodium vanadate (Na 5 V 12 O 32) nanowires, and the Na 5 V 12 O 32 nanowires along with Ti foil were subsequently dissolved thoroughly with citric acid (0.5 M) and hydrofl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…Chemical sensors are commonly used for the detection of NH 3 [ 33 , 87 , 89 , 92 , 211 , 212 , 213 , 214 , 215 , 216 , 217 , 218 ], volatile organic compounds [ 31 , 106 , 219 , 220 , 221 ], variation in pH values [ 81 , 109 , 222 ] and others [ 223 , 224 , 225 , 226 , 227 , 228 ] (see Table 4 ).…”
Section: Application Of Ppy Nanomaterialsmentioning
confidence: 99%
“…Chemical sensors are commonly used for the detection of NH 3 [ 33 , 87 , 89 , 92 , 211 , 212 , 213 , 214 , 215 , 216 , 217 , 218 ], volatile organic compounds [ 31 , 106 , 219 , 220 , 221 ], variation in pH values [ 81 , 109 , 222 ] and others [ 223 , 224 , 225 , 226 , 227 , 228 ] (see Table 4 ).…”
Section: Application Of Ppy Nanomaterialsmentioning
confidence: 99%
“…The properties that make ICPs interesting are electrical conductivity, low weight, processability, corrosion and chemical resistance, biocompatibility, and low cost . Thanks to these features, conductive polymers have found applications in various fields, such as light emitting diodes, solar cells, electronic paper, sensors, tissue engineering, drug delivery, electrochromic devices, and batteries . The most important ICPs are polypyrrole (PPy), polyaniline (PANI), polythiophene (PTh), and their derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…[157,158] Li et al demonstrated an NH 3 sensor using a freestanding PPY/ Na 5 V 12 O 32 fibers composite where they first synthesized Na 5 V 12 O 32 upon which PPY was polymerized. [158] Na 5 V 12 O 32 was prepared by mixing NH 4 VO 3 and NaCl to a molar ratio of 1:6 in deionized (DI) water and transferred to a stainless steel autoclave. Then a Ti foil was inserted and the hydrothermal reaction was carried out for one hour at 150 °C and naturally cooled to room temperature.…”
Section: Polypyrrole-based Ammonia Sensorsmentioning
confidence: 99%